Research on Risk Control in Coffee Milk Beverage Production Based on HACCP and FMEA - Wang Zihang (BIO Web of Conferences)
This study aims to identify hazards and potential risks at each stage of coffee milk beverage production through a combined approach of HACCP (Hazard Analysis and Critical Control Points) and FMEA (Failure Mode and Effects Analysis). It proposes risk control measures and determines the production process's CCPs (Critical Control Points). The analysis of the production process categorizes it into five parts: “Raw Materials and Auxiliary Materials Inspection”, “Preprocessing of Coffee Milk Beverages”, “Post-Processing of Coffee Milk Beverages”, “Physical Hazard Detection”, and “Allergen Hazard Prevention.” Through the CCP decision tree and RPN value calculation, hazards, including physical, chemical, biological, and allergenic hazards, were accurately identified. The results show seven CCPs in coffee milk beverage production. First, chemical hazards from pesticide residues, heavy metal contamination, and excessive food additives during raw material acceptance and mixing. Second, biological hazards from mycotoxins and pathogenic bacteria during roasting and sterilization. Third, physical hazards from metal and plastic residues and allergenic hazards from allergens during processing and packaging. Finally, the study presents specific prevention and corrective plans using HACCP teams and planning charts, effectively reducing production risks and ensuring product quality and consumer safety.